Efek Anti Diabetes Spirulina Platensis Terhadap Analisis Kadar, Gambaran Histopatologi, Ekspresi Insulin dan Glucose Transpoter 4 Pada Tikus Putih Wistar yang Diinduksi Streptozopin - Kintoko Kintoko; Rifqi Ferry Balfas; Nura Ustrina; Sitarina Widyarini; Lintang Cahya Saputri; Anandita Nurwijayanti; Fajar Slamet Riana; Neni Tri Anggraini (Fakultas Farmasi Universitas Pancasila, 2018)
Based on Basic Health Research, in Yogyakarta the incidence of diabetes mellitus based on doctor's diagnosis is 2.6% and symptoms will increase with age, but will decrease from age> 65 years. In the treatment of diabetes mellitus there are several treatments with synthetic drugs and natural ingredients for natural ingredients such as Spirulina platensis. Spirulina platensis is one of the microalgae that contains the natural spectrum of carotene and xantophyll pigment mixtures, and with fikocyanin has antioxidant activity, and Spirulina platensis can show a decrease in blood sugar. The type of research conducted is an experimental study. Spirulina platensis is made with several doses of 36 mg, 72 mg, and 144 mg. Rats were divided into 6 groups, 5 groups of streptozotosin induced at a dose of 45 mg / kgBW until the mice had DM were characterized by high KGD yield, then given spirulina suspension, measured in sugar levels on days 0-28. After that the mice in the blood and then analyzed the effect of Spirulina platensis on creatinine and urea in blood. The results were analyzed using SPSS ANOVA and Post Hoc Test methods with 95% confidence level. The results of the analysis of levels in various groups showed that in the induction of streptozotocin treated with spirulina plantesis various doses there was improvement in each analysis of the levels obtained, and also at the dose STZ+SP 36 in each analysis can improve the level of analysis. While on histopathology result and insulin expression in pancreas and histology and expression of glucose transporter 4 and histopathology on kidney and liver showed good change at various treatment dose group especially in STZ+SP 36 group. So at STZ+SP 36 dose showing the change both in this study.